12-Month Post-Discharge Liver Function Test Abnormalities Among Patients With COVID-19: A Single-Center Prospective Cohort Study - Liao, Xuejiao; Li, Dapeng; Ma, Zhenghua; Zhang, Lina; Zheng, Baoqi; Li, Zhiyan; Li, Guobao; Liu, Lei; Zhang, Zheng (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: The longitudinal effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on the liver are unknown. This study aimed to characterize dynamic changes in liver function test abnormalities in patients with COVID-19 at the acute phase and recovery phase. Methods: A prospective cohort study involved patients with COVID-19 who were admitted to Shenzhen Third People's Hospital between January 11, 2020, and April 27, 2020. Patients underwent liver function tests at hospitalization and at the outpatient visit at the 1-month, 3-month, 6-month, and 12-month follow-ups. Results: Among 461 patients, 28.4% of patients had any kind of liver function tests abnormality at admission, manifested as elevated ALT (13.0%), AST (17.6%), and GGT (15.8%) levels. The trajectory analysis indicated a marked improvement in liver function after discharge, with any kind of liver function test abnormalities of 25.1% at 1 month, 13.2% at 3 months, 16.7% at 6 months, and 13.2% at 12 months after discharge. Persistent liver function abnormalities were observed in patients with pre-existing conditions during follow-up. A significantly higher prevalence of ultrasound determined fatty liver disease was found in those patients with more frequent LFT abnormalities at follow-up. Conclusion: In this study of patients with COVID-19, liver damage in COVID-19 was usually temporary and could return to normal at the end of the 12-month follow-up.